Hypopressive abdominal gymnastics protocol in postpartum women after cesarean section in the remote period: Preliminary case series: Hypopressive abdominal gymnastics in postpartum women - Aguiar, Natália; Kilian, Cristiane; P. D. M. Gonçalves, Ester; Cintas, Janaína; Moraes, Melissa; T. da Luz, Soraia Cristina; da S. Honório, Gesilani Júlia (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: The postpartum period is pronounced by important changes to return to the pre-pregnancy situation. During pregnancy, the recumbent muscles of the abdomen suffer withdrawal, characterizing diastasis of the rectus abdominis muscles (DRAM), and this condition may remain pathological postpartum. Hypopressive abdominal gymnastics (HAG) has a beneficial role in activating the abdominal muscles, presenting positive results in reducing DRAM. Objective: To describe the effect of a HAG protocol in postpartum women undergoing cesarean section in the remote period, comparing the inter-rectum distance (IRD) and abdominal circumference before and after applying the protocol. Methods: Case series quasi-experimental character involving participants had their IRD assessed using a portable ultrasound machine with a linear transducer and abdominal circumference measured using a flexible measuring tape. They received a HAG protocol, with nine postures, for three weeks, twice a week, totaling six sessions lasting 45 to 60 minutes each. After intervention, all participants were reevaluated using the same methods. Results: Four postpartum women participated. The largest point before intervention was the umbilical at rest. Both supraumbilical points analyzed obtained greater results in reducing IRD. Participant 001 achieved the greatest reduction in IRD after the protocol, as she had higher IRD values ​​during evaluation, in addition to a high body mass index (BMI) and a largest measurement of abdominal circumference. The measurement of abdominal circumference showed a change after HAG, reaching a reduction of 10 cm in one of the participants. Conclusion: This case series demonstrated positive results from the practice of HAG in reducing RAD, mainly supra-umbilical, and also in reducing abdominal circumference. Participants with higher BMI and waist circumference showed greater reductions in IRD.